Evaluating the performance of a virtual platform ‘T-BOM’ for mentorship in tropical diseases research among early career scientists: Insights from a pilot in Nigeria and other resource-limited settings - Hammed Oladeji Mogaji; Akan Itinah; Oyinkansola Suliat Fadiji; Olamide Olaitan Omitola; Tawkalitu Eniola Mogaji; Olajide Murtala Keshinro; Falilat Eniola Mogaji; Mahmud Umar Ali; Moses Aikins; Franklin N. Glozah; Dako-Gyeke Phyllis; Uwem Friday Ekpo (Parasite Epidemiology and Control)
Background: Research mentorship plays a crucial role in advancing science. However, there are limited virtual platforms for cultivating mentorship among early career infectious diseases researchers in resource challenged settings. This study reports the findings from the utilization of a recently developed virtual mentorship platform, including its achievements, challenges and needs. Methods: We developed a web-based application called Top-Bottom Open Mentorship (TBOM) freely accessible at www.tbommodel.com. The platform hosts mentors and allows mentees to send connection requests. In this paper, we present the utilization of this platform, including the opportunities and challenges encountered during the first year of implementation. Utilization data was generated monthly, while opportunities and challenges were captured using a users' perception survey. Data were analyzed in R software and summarized thematically as appropriate. Results: Between October 2022 and November 2023, the platform registered 81 users, comprising 63 mentees [54.3 % males, 75 % graduate students] from five countries [Nigeria, Cameroon, Brazil, Sudan, and Ghana], and 18 mentors [78 % males] from six countries [Nigeria, USA, Cameroon, Kenya, Brazil, and Tanzania]. Platform engagement increased from 19.4 % (7 users out of 36 who registered) to 51 % (41 users out of 81 who registered) over the year. Also, a total of 16 mentorship cycles were completed, with 9 currently running. Mentees reported having access to job opportunities, enhanced skills in writing, time management, and grant sourcing, and improved research prospects. However, challenges identified include time zone differences, limited number of mentors, mentee's readiness, and associated internet connection issues. Interpretation: The achievements of T-BOM over a period of one-year are challenged by intrinsic factors from both mentees and mentors, as well as erratic internet services in resource-limited settings. While the platform offers significant opportunities for improving research mentorship, these challenges need to be carefully addressed.